A Dynamic Access Control With Binary Key-Pair - Islam, Md. Rafiqul (Malaysian Journal of Computer Science, 1997)
Based on the concept of an access control matrix, a new dynamic access control scheme with binary key-pair is proposed, which is different from those based on concept of key-lock pairs. In the proposed scheme, each user is assigned a pair of binary keys, which are derived from the access rights with respect to the files. The derivation of the access rights is simple. The method has a special feature, a file or user can be added to or removed from the system without much effort.